Розв’язання двоїстої задачі оптимального керування нормальними режимами ЕЕС з застосуванням нейро-нечіткого моделювання - Петрушенко, О.Ю.; Петрушенко, Ю.В.; Рубаненко, О.О. (Технічна електродинаміка, 2012)
Analyzed the possibility of dvoistoy problem solving of the optimal control normal regimes of EPS with using neurofuzzy modeling. Proposed algorithm of dvoistoy problem solving of the optimal control normal regimes of EPS. This algorithm based on presentation of basis similarity criterion with use function membership in the target function (planned power loss) of propering sets.